The meaning of youth life in traffic violation prevention - Maya Mashita Rachmi; Firman Firman (RedWhite Press, 2020)
The high rate of traffic violations and accidents among adolescents is a real problem, especially when no effective solution has been found to reduce these violations. In fact, from year to year, cases of traffic violations among teenagers are increasing. The purpose of this study is to measure the meaning of adolescent life in traffic violation prevention. This type of research is a descriptive study with a quantitative approach, using a data collection tool in the form of a meaningful life questionnaire with a validity greater than 0.361 and a reliability of 0.964. The subjects of this study were vocational high school students. Subjects were taken using simple random sampling technique. This study uses data analysis techniques with descriptive analysis. The results of this study indicate that the meaning of student life consists of various aspects. Each aspect has a different percentage. The aspect of freedom of will has the lowest percentage of 10%, the aspect of decency of life has a percentage of 12%, the aspect of attitude towards death has a percentage of 23% and the aspect of purpose / meaning of life has the highest percentage of 42%. The results of this study can be used as information for counseling teachers or counselors as a basis for efforts to provide assistance to students to increase the meaning of life in order to prevent negative behavior, one of which is traffic violations that often occur in adolescents.